The Altars of Postmodernity and the Metastasis of the World. A vision of Religion beyond Peter L. Berger and Ulrich Beck (Journal of the Sociology and Theory of Religion, 2018)
We take as a starting point the final point, both biographical and bibliographic, of two of the most important authors of the twentieth century in the reflection on religion, Peter L. Berger and Ulrich Beck. His posthumous works, in the case of Beck literally, have allowed us to carry out a reflection on this fin-de-siècle time par excellence. According to Beck we are facing the metamorphosis of the world in which we live, hence the reflexive devices that we have to think about the changes of the world, because it is a radical transformation, a metamorphosis. According to Berger, we would be facing a new paradigm to understand the world and religion within the constitutive pluralism of modernity. However, I think that what we are facing is the metastasis of a world that reaches the final phase of a long illness, capitalism, which has its senile moment in neoliberalism and in the Postmodern Global Empire its definitive project for an extension that seems impossible, given the physical limits of a world almost devastated by the model of capitalist production and consumption.
Keywords: Modernity; Postmodern Global Empire; Postmodernity; Religion; Secularization; Weak Secularization